Modeling of the process of oilseed meat cooking in a multi-vat cooker during processing of oil raw materials - Didur, Vladimir; Tkachenko, Valentin; Tkachenko, Alexander; Didur, Vladimir; Aseev, Anatolyi (Eastern-European Journal of Enterprise Technologies, 2017)
A new method for determining design and technological parameters and the number of cooker vats for the moisture-thermal oilseed meat treatment has been proposed. The peculiarity of this technique is that the set values of the mean and mean-square oilseed meat moisture were taken as the criteria for the validity of the calculated data. A mathematical model of hydrodynamics of motion of the oilseed meat particles in the cooker vat was developed as a single process of motion of the oilseed meat fluxes along the horizontal concentric circles and along the vertical (meridian) ones traversing the vat axis. The basis of the model is the differential equation of particle motion along the blade rotating around the axis over the heated bottom of the cooker vat. The equation takes into account the design features of the stirrer, speed of blade rotation, length of the blades and physical characteristics of the oilseed meat expressed in terms of friction coefficients. Solution of the equation makes it possible to determine velocity of the particle in the direction of the blade and the circumferential velocity, the time of motion along the blade. This is the initial data for the axial movement of the oilseed meat. The time of passage of the oilseed meat along the agitator blade makes it possible to justify conditions of conductive heat exchange. The time of passage along the vat axis makes it possible to justify the conditions of convective heat exchange. A discrete model of the moving contact layer of the oilseed meat at the hot surface of the vat bottom was developed. Moisture content of the oilseed meat was described by a matrix in which the number of rows is equal to the number of elementary layers and the number of columns is equal to the number of elementary time intervals. The mass of the dry oilseed meat substance is determined by the row vector of the matter mass in the thick layer. Thermal balance of conductive and convective heat and mass transfer of the oilseed meat drying process has been compiled taking into account the heat spent for removal of the bound moisture from the solid phase which will ensure more accurate calculation of the technological conditions of cooking.